2022
DOI: 10.1111/inm.12996
|View full text |Cite
|
Sign up to set email alerts
|

Shared trauma during the COVID‐19 pandemic: Psychological effects on Israeli mental health nurses

Abstract: Mental health nurses, tasked with the constant care of clients undergoing mental health treatment, have faced unique challenges arising from the uncertain outcomes of the COVID-19 pandemic. The shared exposure of both nurses and their patients to a traumatic event such this pandemic leads to additional challenges and ways of coping. The psychological effects of this shared trauma on mental health nurses arising from the pandemic are the subject of this study. An online survey was used to examine personal level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 48 publications
2
18
1
Order By: Relevance
“…Authors' referred to knowledge of resilience derived from several fields including psychology ( n = 5; Chang et al, 2019; Delgado et al, 2020; Delgado et al, 2021; Delgado et al, 2022; Foster et al, 2020), nursing ( n = 5; Dahan et al, 2022; Dogan & Boyacıoglu, 2021; Henshall et al, 2020;Majrabi et al, 2021; Xu et al, 2021), both nursing and psychology ( n = 4; Abram & Jacobowitz, 2021; Dehvan et al, 2018; Ramalisa et al, 2018; Xu et al, 2022) and mental health nursing (Sukut et al, 2022). One study acknowledged there is a lack of an agreed definition of resilience in mental health nursing (Delgado et al, 2020), and two others noted that the primary focus of resilience research in mental health nursing has been on individual resilience rather than inclusive of its complex and multidimensional nature (Dahan et al, 2022; Delgado et al, 2020). Several studies identified that personal resilience was dependent on sociocultural context and that cultural differences in understandings and expressions of resilience might result in variation in resilience scores between studies (Chang et al, 2019; Dahan et al, 2022; Dehvan et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Authors' referred to knowledge of resilience derived from several fields including psychology ( n = 5; Chang et al, 2019; Delgado et al, 2020; Delgado et al, 2021; Delgado et al, 2022; Foster et al, 2020), nursing ( n = 5; Dahan et al, 2022; Dogan & Boyacıoglu, 2021; Henshall et al, 2020;Majrabi et al, 2021; Xu et al, 2021), both nursing and psychology ( n = 4; Abram & Jacobowitz, 2021; Dehvan et al, 2018; Ramalisa et al, 2018; Xu et al, 2022) and mental health nursing (Sukut et al, 2022). One study acknowledged there is a lack of an agreed definition of resilience in mental health nursing (Delgado et al, 2020), and two others noted that the primary focus of resilience research in mental health nursing has been on individual resilience rather than inclusive of its complex and multidimensional nature (Dahan et al, 2022; Delgado et al, 2020). Several studies identified that personal resilience was dependent on sociocultural context and that cultural differences in understandings and expressions of resilience might result in variation in resilience scores between studies (Chang et al, 2019; Dahan et al, 2022; Dehvan et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…One study acknowledged there is a lack of an agreed definition of resilience in mental health nursing (Delgado et al, 2020), and two others noted that the primary focus of resilience research in mental health nursing has been on individual resilience rather than inclusive of its complex and multidimensional nature (Dahan et al, 2022; Delgado et al, 2020). Several studies identified that personal resilience was dependent on sociocultural context and that cultural differences in understandings and expressions of resilience might result in variation in resilience scores between studies (Chang et al, 2019; Dahan et al, 2022; Dehvan et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A second branch of studies has explored the impact of vicarious exposure created by working with traumatized populations, including various negative effects as well as PTG ( Cohen and Collens, 2013 ). Recently, studies have also examined PTG in the context of a shared traumatic reality ( Baum, 2014 ), i.e., when professionals experience the same traumatic event or series of events alongside their clients ( Finklestein and Laufer, 2021 ; Dahan et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%